Propuesta de un tensoactivo de origen vegetal como sustituto parcial de materiales derivados del petróleo en la fabricación de crema lavaloza en la planta de aseo la joya, Casaluker S.A. (2024)
"The substitution of petroleum-derived materials by plant-based alternatives in household hygiene products contributes to the preservation of the environment and society, so this work focuses on the implementation of plant-based surfactants such as Hydroxysultaines, Alkylpolyglucosides and Sulfonated Alpha Olefins in La Joya dishwashing cream produced by Casa Luker S.A. based on the characterization of the product and research into the properties of each surfactant molecule, in order to propose the design of prototype experiments in relation to the petrochemical surfactant. When incorporating each surfactant, the importance of the synergy of the chemical character of each molecule was determined, so Sulfonated Alpha Olefin was selected as the partial substitute for sulfonic acid in 15% of the formulation, where its behavior was evaluated in a batch of 900 kg, in order to determine the productive viability of this material, which influenced production times, packaging and setting of La Joya dishwashing cream due to the fluidity that this provided to the mixture, as well as its performance, reaching a dirt removal level of 10.5 plates. In terms of its economic viability, this alternative reduces the cost/kilo of the formulation by 1%, so when faced with significant manufacturing volumes, its financial viability increases."